Factor:

4y(3x + 2) − 2(3x + 2) =

4y(3x + 2) − 2(3x + 2) =

`_________`

Factor:

4y(3x + 2) − 2(3x + 2) =

4y(3x + 2) − 2(3x + 2) =

`_________`

Detailed Explanation

Any part of an expression that is common to every term in the expression can be factored out. In this case, (3x + 2) is a common term and can be factored out from both parts of the expression:

4y(3x + 2) − 2(3x + 2)

= (3x + 2)(4y − 2)

Notice that distributing (3x + 2) through [4y − 2] yields the original expression; this verifies the answer.

4y(3x + 2) − 2(3x + 2)

= (3x + 2)(4y − 2)

Notice that distributing (3x + 2) through [4y − 2] yields the original expression; this verifies the answer.